ANALISIS DAMPAK KENAIKAN HARGA EMAS TERHADAP STABILITAS MONETER DI INDONESIA - Desty Ika Enjellina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Monetary stability is a key element in maintaining the health of the national economy, as measured by indicators such as inflation, the rupiah exchange rate, interest rates, and the money supply. One of the external factors that affects monetary stability is the fluctuation of gold prices, which act as a safe haven asset in the face of economic intimidation. This study aims to analyze the impact of rising gold prices on monetary stability in Indonesia. The approach used is quantitative with the time series data analysis method and the Error Correction Model (ECM) estimation model, with monthly data from January 2005 to December 2024. The results of the study show that the increase in gold prices has a significant effect on inflation, exchange rates, and interest rate policy in Indonesia. Gold not only triggers sectoral inflation through increasing jewelry prices, but also has an impact on the depreciation of the rupiah due to capital flows and changes in people's investment preferences. In the long term, the soaring gold price also affects the monetary policy response, especially in controlling inflation and stabilizing the exchange rate. Based on these findings, it is recommended that the monetary authorities strengthen the coordination of fiscal and monetary policies, encourage the development of the domestic gold industry, and consider the establishment of the Indonesian Gold Bank as a strategy to increase national economic resilience and maintain monetary stability.